Penerapan Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah pada Laporan Keuangan Pabrik Tempe Rumahan: UMKM Desa Pekan Tolan Kabupaten Labuhan Batu Selatan - Nst, Nur Kamelia; Rokan, Mustapa Khamal; Nurwani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
MSMEs have been chosen by many people to be free from social problems. The recording of MSME financial statements must comply with the Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM). However, many MSMEs, such as Pekan Tolan Village, do not have financial reporting standards. This study aims to understand how the home tempeh factory collects and presents financial data and how the home tempeh factory implements the applicable standards. This study uses a descriptive descriptive approach as an appropriate methodology for in-depth interviews and observations. This research was conducted in a temporary housing factory in Pekan Tolan Village, Kampung Rakyat Village, Labuhan Batu Selatan District. The results of the study show that the home tempe factory in recording financial reports is still done manually and is very simple, and its implementation is not fully in accordance with the provisions stipulated in the EMKM SAK. The recording of the financial statements presented by the home tempeh factory is only a profit and loss statement, while the statement of financial position and notes on financial statements do not yet exist, due to several obstacles that cause SAK EMKM not to be implemented in home tempeh factories, namely a lack of knowledge and understanding of the presentation of appropriate financial statements with Accounting Standards for Small, Medium Companies, ha (SASK EMKM) (SAK EMKM). Keywords: SAK EMKM, UMKM, Financial Statements.